Perovskite solar cell and preparation method thereof
Patent Information
- Application Number
- CN202510448545.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2026-10-20
AI Technical Summary
[0003]钙钛矿(ABX3)太阳能电池制备过程中,较为影响器件性能即为钙钛矿薄膜,制备过程中,结晶速率较快,缺陷较多,会影响载流子传输效率,阻碍其光电转化效率
[0077](1)本发明通过对钙钛矿太阳能电池的结构进行设计,进一步通过在钙钛矿吸光层和第二载流子传输层之间设置界面钝化层,并对界面钝化层的材料进行设计,通过1,4,8,11-四氮杂环十四烷中的含氮键与钙钛矿表面未成键的Pb2+的螯合,以及新引入的钝化基团与钙钛矿吸光层的相互作用,减少了钙钛矿吸光层表面的铅缺陷,提高了钙钛矿太阳能电池的电学性能,其开路电压Voc为1.12-1.14V,短路电流密度Jsc为24.5-25.5mA/cm2,填充因子FF为77.4-80.4%,光电转换效率PCE为21.3-23.0%。
Smart Images

Figure BDA0005353327480000021 
Figure BDA0005353327480000041 
Figure BDA0005353327480000042
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solar cell technology, specifically relating to a perovskite solar cell and its preparation method. Background Technology
[0002] With the continuous development of human society, the demand for energy is increasing. Traditional energy sources, such as oil, natural gas, and coal, are non-renewable. Not only are their reserves dwindling, but they also cause significant environmental pollution. Therefore, vigorously developing renewable, green, and clean energy is extremely urgent and important. Solar energy stands out in particular, as it is inexhaustible and does not impact the environment. Its application research has received increasing attention. Developing clean, pollution-free, and abundant solar energy has become a hot topic of research for scientists. Organic-inorganic hybrid perovskite solar cells, due to their significant advantages such as low cost, high conversion efficiency, and suitability for industrial production, have seen their photoelectric conversion efficiency rapidly rise to 26.41% since their introduction in 2009.
[0003] In the fabrication of perovskite (ABX3) solar cells, the perovskite thin film significantly impacts device performance. During fabrication, a rapid crystallization rate and numerous defects can affect carrier transport efficiency and hinder photoelectric conversion efficiency. Among these defects, unbonded Pb on the perovskite surface is particularly problematic. 2+ This is the primary cause of defects. A good way to solve this problem is to use some interface passivating materials before and after preparing the perovskite thin film. By utilizing the interaction between these materials and the perovskite material, various defects can be reduced, and stability and photoelectric conversion efficiency can be improved.
[0004] Therefore, how to provide a novel, high-performance interface passivation material, and utilize the interaction between this interface passivation material and the perovskite material to reduce various defects in the perovskite layer and improve the stability and photoelectric conversion efficiency of perovskite solar cells, has become an urgent technical problem to be solved. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a perovskite solar cell and its fabrication method. The present invention involves setting an interface passivation layer on one side of the perovskite light-absorbing layer in the perovskite solar cell, and designing the material of the interface passivation layer to include a compound of formula I. By utilizing the interaction between this interface passivation material and the perovskite material, various defects in the perovskite layer are reduced, thereby improving the stability and photoelectric conversion efficiency of the perovskite solar cell.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a perovskite solar cell, wherein, from the substrate to the electrode layer, the perovskite solar cell comprises, sequentially disposed, a substrate, a first carrier transport layer, a perovskite light-absorbing layer, an interface passivation layer, a second carrier transport layer, and an electrode layer.
[0008] The material of the interface passivation layer includes compounds having the structure shown in Formula I:
[0009]
[0010] R1-R4 are each independently selected from any one of -OH, -COOH, -NH2, -CN, -SH, -SO3H, -F, -Cl, -Br, -I, -CHO, -O-CH3, -O-C2H5 or -PO3H2;
[0011] n1-n4 each independently represent integers from 0 to 5, and n1-n4 are not all 0 at the same time.
[0012] This invention provides an interface passivation layer on one side of the perovskite light-absorbing layer in a perovskite solar cell, and designs the material of the interface passivation layer to include a compound of formula I. By utilizing the interaction between the interface passivation material and the perovskite material, various defects in the perovskite layer are reduced, thereby improving the stability and photoelectric conversion efficiency of the perovskite solar cell.
[0013] This invention, by introducing passivating groups (such as -OH, -COOH, -NH2, -CN, -SH, -SO3H, etc.) onto 1,4,8,11-tetraazacyclotetradecane, can largely solve the problem of Pb. 2+ The problem lies in the nitrogen-containing atom in 1,4,8,11-tetraazacyclotetradecane, which can bind to unbonded Pb atoms on the perovskite surface. 2+ Chelation, to obtain This method reduces lead defects and suppresses non-radiative recombination. The newly introduced passivation groups can form hydrogen bonds with the A-site organic cations in the perovskite, thereby inhibiting ion migration and improving cell efficiency. The combined effect of these two factors significantly improves the film quality and stability of the perovskite. Perovskite solar cells treated with this interface passivation material exhibit excellent performance.
[0014] Furthermore, the introduced passivation groups (such as -OH, -COOH, -NH2, -CN, -SH, -SO3H, -CHO, -O-CH3, -O-C2H5, -PO3H2) can further passivate lead defects on the perovskite surface, or the newly introduced passivation groups (such as -F, -Cl, -Br, -I) can fill halogen vacancies and also improve film quality.
[0015] In this invention, n1-n4 each independently represent an integer from 0 to 5 (such as 0, 1, 2, 3, 4 or 5), and n1-n4 are not all 0 at the same time.
[0016] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0017] In a preferred embodiment of the present invention, n1-n4 all represent 1.
[0018] As a preferred embodiment of the present invention, the compound of formula I includes a compound having the structure shown in formula I-1 as follows:
[0019]
[0020] R1-R4 are each independently selected from any one of -OH, -COOH, -NH2, -CN, -SH, -SO3H, -F, -Cl, -Br, -I, -CHO, -O-CH3, -O-C2H5 or -PO3H2.
[0021] Preferably, the material of the interface passivation layer includes at least one of the following compounds:
[0022]
[0023]
[0024] This invention further optimizes the overall performance of perovskite solar cells by selecting a compound of formula I with a specific structure as the interface passivation layer material.
[0025] It should be noted that the present invention does not impose any special restrictions on the synthesis method of the compound of Formula I, and commonly used synthesis methods in the art are applicable.
[0026] In this invention, R1-R4 are the same (represented by R1), n1-n4 are the same (represented by n1, and n1 is not 0), and the preparation method of the compound of formula I includes, but is not limited to:
[0027]
[0028] Where R1 and n1 have the same definitions as above;
[0029] X represents a halogen atom, such as -F, -Cl, -Br, or -I;
[0030] The synthesis method is as follows:
[0031] Add 1,4,8,11-tetraazacyclotetradecane (2.3 mmol, 460 mg) sequentially to a two-necked flask. Compound I (11.0 mmol), XPhos (2-bicyclohexylphosphine-2',4',6'-triisopropylbiphenyl) (0.6 mmol, 286 mg), palladium chloride (0.3 mmol, 53 mg), and sodium tert-butoxide (10 mmol, 960 mg) were added. Toluene (30 mL) was then added, and the mixture was refluxed under N2 atmosphere for 24 h. The solvent was then removed by filtration, and the residue was separated with a mixture of ethyl acetate (EA) and water (1:1 v / v). The aqueous phase was then extracted with EA (50 mL × 3), and the organic layer was washed with brine, dried over sodium sulfate, and recrystallized from a mixture of hexane and ethyl acetate (1:1 v / v) to give compound I.
[0032] As a preferred embodiment of the present invention, the thickness of the interface passivation layer is 1-5nm, for example, it can be 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm or 5nm, etc.
[0033] In this invention, a perovskite solar cell with excellent performance was prepared by controlling the thickness of the interface passivation layer within a specific range.
[0034] As a preferred embodiment of the present invention, the thickness of the perovskite light-absorbing layer is 300-700nm, for example, it can be 300nm, 330nm, 360nm, 390nm, 420nm, 460nm, 490nm, 520nm, 550nm, 570nm, 600nm, 630nm, 660nm or 700nm, etc.
[0035] As a preferred embodiment of the present invention, the first carrier transport layer is a hole transport layer, and the second carrier transport layer is an electron transport layer;
[0036] Alternatively, the first carrier transport layer may be an electron transport layer, and the second carrier transport layer may be a hole transport layer.
[0037] The perovskite solar cell provided by this invention comprises, from bottom to top, a substrate, a hole transport layer, a perovskite light-absorbing layer, an interface passivation layer, an electron transport layer, and an electrode layer;
[0038] Alternatively, the perovskite solar cell may include, from bottom to top, a substrate, an electron transport layer, a perovskite light-absorbing layer, an interface passivation layer, a hole transport layer, and an electrode layer.
[0039] It should be noted that there are no special restrictions on the specific choice of substrate in this invention. Commonly used substrates in the art are applicable, including but not limited to: conductive glass or power-generating crystalline silicon cells. If the substrate is selected from conductive glass, the perovskite solar cell included in this invention is a single-junction perovskite solar cell; if the substrate is selected from power-generating crystalline silicon cells, the perovskite solar cell included in this invention is a tandem cell, where the perovskite top cell and the bottom cell (substrate, power-generating crystalline silicon cell) are connected in series to generate electricity.
[0040] This invention does not impose any special limitations on the thickness range of the conductive glass. Commonly used thickness ranges in the art are applicable. The thickness of the conductive glass is exemplary but not limited to: 80-150nm, for example, it can be 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm or 150nm, etc.
[0041] This invention does not have any special design for the structure of the power-generating crystalline silicon cell; it is applicable to all commonly used power-generating crystalline silicon cells in the field.
[0042] In this invention, the hole transport layer can be a p-type semiconductor material, including any one or a combination of at least two of the following: poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD), poly(3,4-ethylenedioxythiophene:polystyrene sulfonate (PEDOT:PSS), 4-butyl-N,N-diphenylaniline homopolymer (Ploy-TPD), polyvinylcarbazole (PVK), NiOx, CuI, and CuSCN.
[0043] In this invention, the thickness of the hole transport layer can be 10 to 50 nm, for example, it can be 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 27 nm, 30 nm, 33 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 49 nm or 50 nm, etc.
[0044] In this invention, the perovskite light-absorbing layer is prepared from a perovskite precursor solution, wherein the perovskite precursor contains ABX3 perovskite material, where A is CH3NH3. + CH(NH2)2 + Cs + or Rb + B is any combination of one or at least two of the following, where B is Pb. 2+ Sn 2+ Or Ge 2+ Any combination of one or at least two of them, X is Cl- ,Br - Or I - The solvent of the perovskite precursor solution includes any one or a combination of at least two of the following: N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), γ-butyrolactone (GBL), 1,3-dimethyl-2-imidazolinone (DMI), dimethylacetamide (DMAC), N,N-dimethylpropenylurea (DMPU), acetonitrile (ACN), or 2-mercaptoethanol (2-ME).
[0045] It should be noted that the present invention does not impose any special restrictions on the mass concentration of perovskite material in the perovskite precursor solution, and the mass concentration range commonly used in the art is applicable.
[0046] In this invention, the material of the electron transport layer can be an n-type semiconductor material, including C 60 Any one of PCBM, BCP, TiO2, SnO2, ZnO, or ZnO-ZnS.
[0047] In this invention, the thickness of the electron transport layer can be 10 to 50 nm, for example, it can be 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 27 nm, 30 nm, 33 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 49 nm or 50 nm, etc.
[0048] In this invention, the electrode layer material can be any one of Al, Au, Ag or carbon electrode.
[0049] In this scheme, the thickness of the electrode layer can be 50 to 150 nm, for example, it can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm or 200 nm, etc.
[0050] In a second aspect, the present invention provides a method for fabricating a perovskite solar cell as described in the first aspect, the method comprising the following steps:
[0051] A first carrier transport layer, a perovskite light-absorbing layer, an interface passivation layer, a second carrier transport layer, and an electrode layer are sequentially disposed on one side of the substrate to obtain the perovskite solar cell.
[0052] As a preferred embodiment of the present invention, the method for setting the interface passivation layer includes the following steps:
[0053] The interface passivation material precursor solution is coated on the side of the perovskite light-absorbing layer away from the first carrier transport layer, and then annealed to obtain the interface passivation layer.
[0054] The interface passivation layer precursor solution includes a compound of formula I as described in the first aspect.
[0055] As a preferred embodiment of the present invention, the concentration of compound of formula I in the interface passivation layer precursor solution is 1-5 mg / mL, for example, it can be 1 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3 mg / mL, 3.5 mg / mL, 4 mg / mL, 4.5 mg / mL or 5 mg / mL, etc.
[0056] Preferably, the solvent of the interface passivation layer precursor solution includes any one or a combination of at least two of isopropanol, toluene, or ethyl acetate.
[0057] In this invention, the coating method includes spin coating.
[0058] Preferably, the spin coating speed is 3000-5000 rpm, for example, it can be 3000 rpm, 3200 rpm, 3400 rpm, 3600 rpm, 3800 rpm, 4000 rpm, 4200 rpm, 4400 rpm, 4600 rpm, 4800 rpm or 5000 rpm.
[0059] Preferably, the spin coating time is 35-45s, for example, it can be 35s, 36s, 37s, 38s, 39s, 40s, 41s, 42s, 43s, 44s or 45s.
[0060] As a preferred embodiment of the present invention, the annealing temperature is 90-110℃ (e.g., 90℃, 92℃, 94℃, 96℃, 98℃, 100℃, 102℃, 104℃, 106℃, 108℃, or 110℃, etc.), and the time is 8-12min (e.g., 8min, 8.5min, 9min, 9.5min, 10min, 10.5min, 11min, 11.5min, or 12min, etc.).
[0061] It should be noted that the present invention does not impose any special limitations on the method of forming a first carrier transport layer, a perovskite light-absorbing layer, a second carrier transport layer, and an electrode layer on one side of the conductive substrate in a perovskite solar cell. Taking a conductive glass substrate, a hole transport layer as the first carrier transport layer, and an electron transport layer as the second carrier transport layer as an example, the fabrication method of the perovskite solar cell exemplarily includes the following steps:
[0062] (1) Pretreatment of the substrate;
[0063] (2) Spin-coating a hole transport material precursor solution onto one side of the substrate and annealing to obtain a hole transport layer;
[0064] (3) Coat the hole transport layer with a perovskite precursor solution on the side away from the substrate, anneal, and form a perovskite layer (thin film light-absorbing layer).
[0065] (4) Spin-coating an interface passivation material precursor solution onto the side of the perovskite layer away from the substrate, and annealing to obtain the interface passivation layer.
[0066] (5) An electron transport layer is provided on the side of the interface passivation layer away from the substrate;
[0067] (6) An electrode layer is disposed on the side of the electron transport layer away from the substrate to obtain the perovskite solar cell.
[0068] Preferably, the pretreatment method in step (1) includes washing (including ultrasonic cleaning with detergent, deionized water, acetone and anhydrous ethanol respectively) and drying (including drying with a nitrogen gun).
[0069] Preferably, the coating method in step (2) includes spin coating, wherein the spin coating speed is 4500-5500 rpm (e.g., 4500 rpm, 4600 rpm, 4700 rpm, 4800 rpm, 4900 rpm, 5000 rpm, 5100 rpm, 5200 rpm, 5300 rpm, 5400 rpm or 5500 rpm, etc.), and the time is 45-55 s (e.g., 45 s, 46 s, 47 s, 48 s, 49 s, 50 s, 51 s, 52 s, 53 s, 54 s or 55 s, etc.).
[0070] Preferably, the annealing temperature in step (2) is 140-160℃ (e.g., 140℃, 142℃, 144℃, 146℃, 148℃, 150℃, 152℃, 154℃, 156℃, 158℃ or 160℃, etc.), and the time is 12-18min (e.g., 12min, 13min, 14min, 15min, 16min, 17min or 18min, etc.).
[0071] Preferably, the coating method in step (3) includes spin coating, wherein the spin coating speed is 4500-5500 rpm (e.g., 4500 rpm, 4600 rpm, 4700 rpm, 4800 rpm, 4900 rpm, 5000 rpm, 5100 rpm, 5200 rpm, 5300 rpm, 5400 rpm or 5500 rpm, etc.), and the time is 45-55 s (e.g., 45 s, 46 s, 47 s, 48 s, 49 s, 50 s, 51 s, 52 s, 53 s, 54 s or 55 s, etc.).
[0072] Preferably, the annealing temperature in step (3) is 110-130℃ (e.g., 110℃, 112℃, 114℃, 116℃, 118℃, 120℃, 122℃, 124℃, 126℃, 128℃ or 130℃, etc.), and the time is 12-18min (e.g., 12min, 13min, 14min, 15min, 16min, 17min or 18min, etc.).
[0073] Preferably, the method for setting the electron transport layer in step (5) includes vacuum evaporation.
[0074] Preferably, the method for setting the electrode layer in step (6) includes vacuum evaporation.
[0075] It should be noted that the present invention does not impose any special restrictions on the process conditions of vacuum evaporation when setting electron transport layers and electrode layers by vacuum evaporation, and the process conditions commonly used in the art are applicable.
[0076] Compared with the prior art, the present invention has the following beneficial effects:
[0077] (1) This invention designs the structure of a perovskite solar cell, further sets an interface passivation layer between the perovskite light-absorbing layer and the second carrier transport layer, and designs the material of the interface passivation layer so that the nitrogen-containing bonds in 1,4,8,11-tetraazacyclotetradecane are bonded to the unbonded Pb on the perovskite surface. 2+ The chelation effect and the interaction between the newly introduced passivating groups and the perovskite light-absorbing layer reduce lead defects on the surface of the perovskite light-absorbing layer, thereby improving the electrical performance of the perovskite solar cell. Its open-circuit voltage Voc is 1.12-1.14V, and its short-circuit current density Jsc is 24.5-25.5mA / cm². 2 The fill factor (FF) is 77.4-80.4%, and the photoelectric conversion efficiency (PCE) is 21.3-23.0%.
[0078] (2) By further controlling the thickness of the interface passivation layer within a specific range, this invention further improves the overall performance of perovskite solar cells, with an open-circuit voltage Voc of 1.12-1.14V and a short-circuit current density Jsc of 24.8-25.5mA / cm². 2 The fill factor (FF) is 79.7-80.4%, and the photoelectric conversion efficiency (PCE) is 22.8-23.0%. Attached Figure Description
[0079] Figure 1 These are XRD patterns of the perovskite light-absorbing layer in the perovskite solar cells provided in Examples 1-4 and Comparative Example 1 of this invention;
[0080] Figure 2 These are the ultraviolet spectra of the perovskite light-absorbing layer in the perovskite solar cells provided in Embodiment 1 and Comparative Example 1 of the present invention;
[0081] Figure 3 These are fluorescence spectra of the perovskite light-absorbing layer in the perovskite solar cells provided in Embodiment 1 and Comparative Example 1 of the present invention;
[0082] Figure 4 This is a comparison chart of the JV curves of the perovskite solar cells provided in Embodiment 1 and Comparative Example 1 of the present invention.
[0083] Figure 5 The perovskite solar cells provided in Examples 1-4 and Comparative Example 1 of this invention were immersed in water for 8 hours, and the Pb content in the water was [not specified]. 2+ The concentration test characterization results. Detailed Implementation
[0084] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be considered as specific limitations thereof.
[0085] The sources of some components in the following examples and comparative examples are as follows:
[0086] Transparent conductive substrate: purchased from Liaoning Youxuan, item number: YXKJPI-0002;
[0087] Preparation Example 1
[0088] This preparation example provides a method for synthesizing compound A, the structural formula of which is:
[0089]
[0090] The synthesis method is as follows:
[0091] In a double-necked flask, 1,4,8,11-tetraazacyclotetradecane (2.3 mmol, 460 mg), 4-bromobenzoic acid (11.0 mmol), XPhos (0.6 mmol, 286 mg), palladium chloride (0.3 mmol, 53 mg), and sodium tert-butoxide (10 mmol, 960 mg) were added sequentially, followed by the addition of toluene (30 mL). The mixture was refluxed under a nitrogen atmosphere for 24 h, and then filtered to remove the solvent. The residue was separated with a mixture of ethyl acetate (EA) and water (1:1 v / v). The aqueous phase was then extracted with EA (50 mL × 3), and the organic layer was washed with brine. The residue was dried with sodium sulfate and recrystallized with a mixture of hexane and ethyl acetate (1:1 v / v) to give compound A.
[0092] Preparation Example 2
[0093] This preparation example provides a method for synthesizing compound B, the structural formula of which is:
[0094]
[0095] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equal amount of 4-bromophenol, and the other conditions are the same as in Preparation Example 1.
[0096] Preparation Example 3
[0097] This preparation example provides a method for synthesizing compound C, the structural formula of which is:
[0098]
[0099] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equal amount of 4-bromobenzonitrile, and the other conditions are the same as those in Preparation Example 1.
[0100] Preparation Example 4
[0101] This preparation example provides a method for synthesizing compound D, the structural formula of which is:
[0102]
[0103] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equal amount of 4-bromobenzenesulfonic acid, and the other conditions are the same as in Preparation Example 1.
[0104] Preparation Example 5
[0105] This preparation example provides a method for synthesizing compound E, the structural formula of which is:
[0106]
[0107] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equimolar amount of... Other conditions are the same as in Preparation Example 1.
[0108] Preparation Example 6
[0109] This preparation example provides a method for synthesizing compound F, the structural formula of which is:
[0110]
[0111] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equimolar amount of... Other conditions are the same as in Preparation Example 1.
[0112] Preparation Example 7
[0113] This preparation example provides a method for synthesizing compound G, the structural formula of which is:
[0114]
[0115] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equimolar amount of... Other conditions are the same as in Preparation Example 1.
[0116] Preparation Example 8
[0117] This preparation example provides a method for synthesizing compound H, whose structural formula is:
[0118]
[0119] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equal amount of p-dibromobenzene, and the other conditions are the same as in Preparation Example 1.
[0120] Preparation Example 9
[0121] This preparation example provides a method for synthesizing compound I, the structural formula of which is:
[0122]
[0123] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equimolar amount of... Other conditions are the same as in Preparation Example 1.
[0124] Preparation Example 10
[0125] This preparation example provides a method for synthesizing compound J, the structural formula of which is:
[0126]
[0127] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equal amount of 4-bromobenzaldehyde, and the other conditions are the same as those in Preparation Example 1.
[0128] Preparation Example 11
[0129] This preparation example provides a method for synthesizing compound K, whose structural formula is:
[0130]
[0131] The synthesis method is the same as that of compound A provided in Preparation Example 1, except that 4-bromobenzoic acid is replaced with an equimolar amount of... Other conditions are the same as in Preparation Example 1.
[0132] Example 1
[0133] This embodiment provides a perovskite solar cell and its fabrication method. The perovskite solar cell includes a conductive substrate, a hole transport layer, a perovskite light-absorbing layer, an interface passivation layer, an electron transport layer, and an electrode layer stacked sequentially.
[0134] The perovskite solar cell is prepared as follows:
[0135] (1) Clean the transparent conductive glass, specifically by ultrasonic cleaning with detergent, deionized water, acetone and anhydrous ethanol respectively, and then drying it with a nitrogen gun; wherein, the ultrasonic cleaning power is 100Hz and the ultrasonic cleaning time is 15min.
[0136] (2) A hole transport layer was deposited on the surface of transparent conductive glass by spin coating. Specifically, a hole transport layer solution with a concentration of 65 mg / mL prepared by PEDOT:PSS (solvent is ultrapure water) was dropped onto the transparent conductive glass and spin coated at a speed of 5000 rpm for 50 s to obtain a hole transport layer with a thickness of 20 nm.
[0137] (3) A perovskite light-absorbing layer is prepared on the upper surface of the hole transport layer, specifically including:
[0138] MAI, FAI, MACl, and PbI2 were dissolved in a mixed solvent composed of dimethyl sulfoxide (DMSO) and dimethylformamide (DMF). The solution was heated at 70°C and stirred continuously for 1 hour to ensure complete dissolution, thus obtaining a perovskite precursor solution. The molar ratio of FAI:MAI:MACl was 0.95:0.05:0.14, the concentrations of FAI and PbI2 were both 1.5M (M is the molar concentration, i.e., mol / L), and the volume ratio of dimethyl sulfoxide (DMSO) to dimethylformamide (DMF) in the mixed solvent was 1:9, with a total volume of 2 mL.
[0139] The perovskite precursor solution was spin-coated onto the hole transport layer at 5000 rpm for 50 seconds. Finally, it was annealed at 120°C for 15 minutes to crystallize and form FA. 0.95 MA 0.05 The PbI3 perovskite light-absorbing layer has a thickness of 450 nm.
[0140] (4) Take 150 μL of 3 mg / mL interface passivation material compound A (solvent is isopropanol) solution and spin-coat it onto the above perovskite film. The spin-coating parameters are 4000 rpm and 40 s. Then anneal at 100 °C for 10 min to obtain an interface passivation layer with a thickness of 3 nm.
[0141] (5) A C layer is deposited on the surface of the perovskite layer by vacuum evaporation. 60 The evaporation is carried out under a vacuum of 5×10⁻⁶. -4 The process was carried out under Pa conditions, with an evaporation rate of [missing information]. Get C 60 The layer is 20nm thick;
[0142] In C 60 A second BCP layer is deposited on the surface of the first layer by vacuum evaporation, wherein the evaporation is performed at a vacuum degree of 5 × 10⁻⁶. -4 The process was carried out under Pa conditions, with an evaporation rate of [missing information]. An electron transport layer with a thickness of 8 nm was obtained;
[0143] (6) A metal electrode is fabricated on the upper surface of the electron transport layer. Specifically, a silver electrode is formed on the surface of the electron transport layer by thermal evaporation in a metal evaporation chamber to obtain an electrode layer with a thickness of 100 nm, thus completing the fabrication of the perovskite solar cell. The vacuum degree of the evaporation chamber is 5 × 10⁻⁶. -4 Pa, evaporation rate is
[0144] Example 2
[0145] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound B; other conditions are the same as in Example 1.
[0146] Example 3
[0147] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound C; other conditions are the same as in Example 1.
[0148] Example 4
[0149] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Embodiment 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound D; other conditions are the same as in Embodiment 1.
[0150] Example 5
[0151] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the concentration of the interface passivation material compound A solution in step (4) is 1 mg / mL, and the thickness of the obtained interface passivation layer is about 1 nm. Other conditions are the same as in Example 1.
[0152] Based on the current testing accuracy, it is difficult to accurately test thicknesses of 1 nm and below. Therefore, the thickness of the interface passivation layer obtained in this embodiment is approximately 1 nm.
[0153] Example 6
[0154] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the concentration of the interface passivation material compound A solution in step (4) is 5 mg / mL, the thickness of the obtained interface passivation layer is 5 nm, and other conditions are the same as in Example 1.
[0155] Example 7
[0156] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the concentration of the interface passivation material compound A solution in step (4) is 0.5 mg / mL, the thickness of the obtained interface passivation layer is <1 nm, and other conditions are the same as in Example 1.
[0157] Example 8
[0158] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the concentration of the interface passivation material compound A solution in step (4) is 6 mg / mL, the thickness of the obtained interface passivation layer is 6 nm, and other conditions are the same as in Example 1.
[0159] Example 9
[0160] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Embodiment 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound E; other conditions are the same as in Embodiment 1.
[0161] Example 10
[0162] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound F; other conditions are the same as in Example 1.
[0163] Example 11
[0164] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Embodiment 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound G; other conditions are the same as in Embodiment 1.
[0165] Example 12
[0166] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound H; other conditions are the same as in Example 1.
[0167] Example 13
[0168] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the interface passivation material compound A in step (4) is replaced with interface passivation material compound I; other conditions are the same as in Example 1.
[0169] Example 14
[0170] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound J; other conditions are the same as in Example 1.
[0171] Example 15
[0172] This embodiment provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that the interface passivation material compound A in step (4) is replaced with the interface passivation material compound K; other conditions are the same as in Example 1.
[0173] Comparative Example 1
[0174] This comparative example provides a perovskite solar cell and its fabrication method. The perovskite solar cell includes a conductive substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, and an electrode layer stacked sequentially.
[0175] The above-mentioned perovskite solar cell preparation method refers to the perovskite solar cell preparation method provided in Example 1, the only difference being that step (4) is not performed; other conditions are the same as in Example 1.
[0176] Comparative Example 2
[0177] This comparative example provides a perovskite solar cell and its preparation method. The only difference from Example 1 is that step (4) in Example 1 is replaced by: dissolving 0.882 mg of 1,4,8,11-tetraazacyclotetradecane, 2.153 mg of benzoic acid, and 1 mL of isopropanol by thorough stirring, taking 150 μL and spin-coating it onto the perovskite film. The spin-coating parameters are 4000 rpm and 40 s. Then, it is annealed at 100 °C for 10 min to obtain an interface passivation layer with a thickness of 3 nm. Other conditions are the same as in Example 1.
[0178] Using Cu Kα As the X-ray source, the scanning range was 2θ = 5°-40°, and the scanning speed was 5° / min. The θ-2θ scanning mode was mainly used to scan and test the perovskite thin film samples (instrument model: Rigaku D / MAX-2500, Japan). The XRD derived peaks of the perovskite light-absorbing layer in the perovskite solar cells provided in Examples 1-4 and Comparative Example 1 were characterized, and their XRD patterns are shown below. Figure 1 As shown. By Figure 1 It can be seen that the XRD diffraction peak positions of the perovskite light-absorbing layer films after treatment with no interface passivation layer (Comparative Example 1) or with different compounds used to set the interface passivation layer (Examples 1-4) are the same, and there are no other impurity peaks, indicating that the interface passivation material has not entered the perovskite lattice. Furthermore, from... Figure 1 As can be seen from the data, the relative height of the PbI2 diffraction peak in the perovskite film was significantly reduced after treatment with the interface passivation layer (Examples 1-4), further indicating that the nitrogen-containing bonds in 1,4,8,11-tetraazacyclotetradecane in the interface passivation material can bind to the unbonded Pb on the perovskite surface. 2+Chelation, and the newly introduced passivating groups (carboxyl / hydroxyl / cyano / sulfonic acid groups) can further passivate lead defects on the surface and reduce non-radiative recombination.
[0179] The ultraviolet spectra of the perovskite absorber layers in the perovskite solar cells provided in Example 1 and Comparative Example 1 were characterized using an ultraviolet spectrometer (UV measurement range 400-900 nm, model: Varian Cary 5000). The ultraviolet spectra are shown below. Figure 2 As shown. By Figure 2 It can be seen that the absorption peak of the perovskite light-absorbing layer film after treatment with the interface passivation layer (Example 1) has a slight red shift. This is mainly because the molecules of the interface passivation material can reduce lead defects, thereby promoting the crystallization of the perovskite film and making the size of the final perovskite larger.
[0180] The fluorescence spectra of the perovskite absorbing layer in the perovskite solar cells provided in Example 1 and Comparative Example 1 of this invention were characterized using a fluorescence spectrometer (Xenon lamp (Xe 900) with a wavelength of 500 nm, model: Edinburgh FLS980 fluorescence spectrometer). The fluorescence spectra are shown below. Figure 3 As shown. By Figure 3 It can be seen that the emission peak of the fluorescence spectrum of the perovskite light-absorbing layer film is significantly improved after the interface passivation layer treatment (Example 1), and the surface non-radiative recombination is further reduced, indicating that the perovskite light-absorbing layer film formation quality is higher.
[0181] The JV curves of the perovskite light-absorbing layer in the perovskite solar cells provided in Example 1 and Comparative Example 1 were characterized using a solar energy simulation testing system from Taiwan Guangyan Technology Co., Ltd. The comparison of their JV curves is shown in the figure below. Figure 4 As shown. By Figure 4 It is evident that the perovskite solar cells formed after treatment exhibit significant improvements in open-circuit voltage, short-circuit current, fill factor, and photoelectric conversion efficiency. This is because the nitrogen-containing atoms in 1,4,8,11-tetraazacyclotetradecane and the newly introduced carboxyl groups can chelate with unbonded Pb²⁺ on the perovskite surface, reducing lead defects and suppressing non-radiative recombination, thereby improving cell efficiency.
[0182] Unencapsulated perovskite solar cells were immersed in a vessel containing 50 mL of deionized water. After 8 hours, 10 mL of water was collected from the vessel, and the sample was analyzed using inductively coupled plasma optical emission spectroscopy (ICP-OES, model: 5100 ICP-OES, Agilent Technologies). The results are as follows: Figure 5 As shown. By Figure 5 It can be seen that the Pb in the water used to soak the perovskite solar cells provided in Comparative Example 1 2+The lead concentration was 0.3632 ppm, while the lead leakage of the perovskite solar cells (Examples 1-4) with the interface passivation layer was greatly improved. This further demonstrates that the nitrogen-containing functional groups in 1,4,8,11-tetraazacyclotetradecane in the interface passivation material can interact with the unbonded Pb on the perovskite surface. 2+ The chelation process, combined with the newly introduced passivating groups, further passivates lead defects on the surface, significantly reducing lead leakage from the battery.
[0183] The performance of the perovskite solar cells provided in the above embodiments and comparative examples was tested and characterized. The specific test methods are as follows:
[0184] Measurements were performed using a solar energy simulation testing system from Taiwan Guangyan Technology Co., Ltd. The light source was a 500W xenon lamp solar spectrum simulator, calibrated with a standard silicon cell KG-5, at a solar intensity (AM 1.5G: 100mW / cm²). 2 Measurements are performed under the following conditions: A continuously varying voltage (-0.5V-1.2V) is applied across the battery terminals, and the battery's output current is measured (using a Keithley 2400 power supply). The product of these two measurements yields the JV test curve, which displays the photoelectric conversion efficiency of the device under different conditions.
[0185] The test data above are shown in Table 1 below:
[0186] Table 1
[0187]
[0188]
[0189] As can be seen from the above, this invention designs the structure of a perovskite solar cell, further sets an interface passivation layer between the perovskite light-absorbing layer and the second carrier transport layer, and designs the material of the interface passivation layer so that the nitrogen-containing bonds in 1,4,8,11-tetraazacyclotetradecane are bonded to the unbonded Pb on the perovskite surface. 2+ The chelation effect and the interaction between the newly introduced passivating groups and the perovskite light-absorbing layer reduce lead defects on the surface of the perovskite light-absorbing layer, thereby improving the electrical performance of the perovskite solar cell. Its open-circuit voltage Voc is 1.12-1.14V, and its short-circuit current density Jsc is 24.5-25.5mA / cm². 2 The fill factor (FF) is 77.4-80.4%, and the photoelectric conversion efficiency (PCE) is 21.3-23.1%.
[0190] As can be seen from Examples 1 and 5-8, by controlling the thickness of the interface passivation layer within a specific range, the present invention further improves the electrical performance of perovskite solar cells, with an open-circuit voltage Voc of 1.12-1.14V and a short-circuit current density Jsc of 24.8-25.5mA / cm². 2 The fill factor (FF) is 79.7-80.4%, and the photoelectric conversion efficiency (PCE) is 22.8-23.0%.
[0191] In summary, this invention, through the design of the structure of a perovskite solar cell, and further by setting an interface passivation layer between the perovskite light-absorbing layer and the second carrier transport layer, and by designing the material of the interface passivation layer, has prepared a perovskite solar cell with excellent performance.
[0192] The applicant declares that the detailed structural features and detailed process flow of the present invention are illustrated through the above embodiments, but the present invention is not limited to the above detailed structural features and detailed process flow, that is, it does not mean that the present invention must rely on the above detailed structural features and detailed process flow to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the components used in the present invention, additions of auxiliary components, selection of specific methods, equivalent substitutions of the raw materials of the product of the present invention, additions of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A perovskite solar cell, characterized in that, From the substrate to the electrode layer, the perovskite solar cell includes a substrate, a first carrier transport layer, a perovskite light-absorbing layer, an interface passivation layer, a second carrier transport layer, and an electrode layer arranged sequentially. The material of the interface passivation layer includes compounds having the structure shown in Formula I: R1-R4 are each independently selected from any one of -OH, -COOH, -NH2, -CN, -SH, -SO3H, -F, -Cl, -Br, -I, -CHO, -O-CH3, -O-C2H5 or -PO3H2; n1-n4 each independently represent integers from 0 to 5, and n1-n4 are not all 0 at the same time.
2. The perovskite solar cell according to claim 1, characterized in that, n1-n4 all represent 1.
3. The perovskite solar cell according to claim 1 or 2, characterized in that, The compounds of Formula I include compounds having the structure shown in Formula I-1: Wherein, R1-R4 are each independently selected from any one of -OH, -COOH, -NH2, -CN, -SH, -SO3H, -F, -Cl, -Br, -I, -CHO, -O-CH3, -O-C2H5, or -PO3H2; preferably, the material of the interface passivation layer includes at least one of the following compounds:
4. The perovskite solar cell according to any one of claims 1-3, characterized in that, The thickness of the interface passivation layer is 1-5 nm.
5. The perovskite solar cell according to any one of claims 1-4, characterized in that, The thickness of the perovskite light-absorbing layer is 300-700 nm.
6. The perovskite solar cell according to any one of claims 1-5, characterized in that, The first carrier transport layer is a hole transport layer, and the second carrier transport layer is an electron transport layer; Alternatively, the first carrier transport layer may be an electron transport layer, and the second carrier transport layer may be a hole transport layer.
7. A method for preparing a perovskite solar cell according to any one of claims 1-6, characterized in that, The preparation method includes the following steps: A first carrier transport layer, a perovskite light-absorbing layer, an interface passivation layer, a second carrier transport layer, and an electrode layer are disposed on one side of the substrate to obtain the perovskite solar cell.
8. The preparation method according to claim 7, characterized in that, The method for setting the interface passivation layer includes the following steps: The interface passivation material precursor solution is coated on the side of the perovskite light-absorbing layer away from the first carrier transport layer, and then annealed to obtain the interface passivation layer. The interface passivation layer precursor solution includes the compound of formula I as described in claim 1.
9. The preparation method according to claim 8, characterized in that, The concentration of compound I in the interface passivation layer precursor solution is 1-5 mg / mL; Preferably, the solvent of the interface passivation layer precursor solution includes any one or a combination of at least two of isopropanol, toluene, or ethyl acetate.
10. The preparation method according to claim 8 or 9, characterized in that, The annealing temperature is 90-110℃ and the time is 8-12 minutes.